MODELS FOR DIRECT TAXATION OF COOPERATIVESUNDER COMPARATIVE LAW - Rubio, Marina Aguilar (International Journal of Cooperative Law, 2025)
The cooperative society is shownto be a corporate formula inspired by different operating principles from those governing the conventional corporation.Based on this special nature that the cooperative has, the paper goes on to analyse its tax treatment,trying to find the answer to two questions.